Aspirin use is associated with increased risk for incident heart failure: a patient‐level pooled analysis. (22nd November 2021) - Mujaj, Blerim; Zhang, Zhen‐Yu; Yang, Wen‐Yi; Thijs, Lutgarde; Wei, Fang‐Fei; Verhamme, Peter; Delles, Christian; Butler, Javed; Sever, Peter; Latini, Roberto; GF Cleland, John; Zannad, Faiez; et al.
Abstract: Aims: Recent trials evaluating the effect of aspirin in the primary prevention of cardiovascular disease showed little or no benefit. However, the role of aspirin on the risk of incident heart failure (HF) remains elusive. This study aimed to evaluate the role of aspirin use on HF incidence in primary and secondary prevention and whether aspirin use increases the risk of incident HF in patients at risk. Methods and results: Data from 30 827 patients at risk for HF enrolled in six observational studies were analysed [women 33.9%, mean age (±standard deviation) 66.8 ± 9.2 years]. Cardiovascular risk factors and aspirin use were recorded at baseline, and patients were followed up for the first incident of fatal or non‐fatal HF. The association of incident HF with aspirin use was assessed using multivariable‐adjusted proportional hazard regression, which accounted for study and cardiovascular risk factors. Over 5.3 years (median; 5th–95th percentile interval, 2.1–11.7 years), 1330 patients experienced HF. The fully adjusted hazard ratio (HR) associated with aspirin use was 1.26 [95% confidence interval (CI) 1.12–1.41; P ≤ 0.001]. Further, in a propensity‐score‐matched analysis, the HR was 1.26 (95% CI 1.10–1.44; P ≤ 0.001). In 22 690 patients (73.6%) without history of cardiovascular disease, the HR was 1.27 (95% CI 1.10–1.46; P = 0.001). Conclusions: In patients, at risk, aspirin use was associated with incident HF, independent of other risk factors. In the absence of conclusive trial evidence, our observations suggest that aspirins should be prescribed with caution in patients at risk of HF or having HF.